Research on the influence of excavation and loading on Z-direction displacement in surrounding soil mass - Li, X.; Zhou, W.; Han, L.; Xi, W.J.; Crusoe, G.E. (Polska Akademia Nauk, 2014)
To probe into the pattern in which the excavation and loading process have on such factors as stress and displacement in neighboring regions of deep open pits, a mechanical unloading model in coal mining process and another model for the loading process are set up respectively. Besides, FLAC(3D) software is used to simulate dynamic excavating and loading process in open pits and record such data as the unbalanced stress, unloading strength and displacement fluctuations, which further serve as basis for studying the functional relationship about different mining heights and scope of influence using fitting method. The research results indicate that the unloading strength enhances with increasing mining depth in a linear fashion. In addition, a noticeable displacement circle takes shape around the stope, which would also extends with growing mining depth. As to waste loading, it brings about large-scale surface subsidence in neighboring regions, which follows a logarithm function convergence pattern with the distance away from the dump border. Under combined effects of excavation and loading, the value of the soil mass displacement would increase with growing mining depth and loading height. Specifically, the soil displacement at a distance of 100 m away from the stope border (around 200 m away from the outer dump border) is abnormally significant and it further develops at a rate of 0.0228 mm/h.